PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP BERNALAR KRITIS DAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATERI PEMBAGIAN - Fauziyah, Fifin; Huda, Nuril; Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The current learning process cannot develop critical reasoning and problem solving abilities optimally because learning is teacher-centred. Learning through lectures is widely used by elementary school teachers because it is easier and does not require complicated preparations. Teacher-centered learning will have an impact on low student involvement in every learning activity. These learning problems need to be overcome by making improvements in various aspects, especially in choosing learning models. Teachers need to choose a learning model that suits the characteristics of elementary school mathematics subjects. One of the recommended mathematics learning models is Realistic Mathematics Education (RME). The objectives of this research include: 1) To prove the influence of the realistic mathematics education (RME) learning model on students' critical reasoning abilities in class II division material at UPTD SDN Labang Bangkalan. To prove the influence of the realistic mathematics education (RME) learning model on problem solving abilities students in class II division material at UPTD SDN Labang Bangkalan. This research is quantitative research with the type of experimental research. The sample for this research was 24 students in class II-A as the experimental group and class II-B as the control group. data were collected using test question instruments and analyzed using the independent sample t test analysis technique to produce the following research conclusions: 1) The realistic mathematics education (RME) learning model influences students' critical reasoning abilities in class II UPTD material at SDN Labang Bangkalan, and 2) The realistic mathematics education (RME) learning model influences students' problem solving abilities in class II division material at UPTD SDN Labang Bangkalan.